Self-Care, a Critical ‘Caregiver’ to the Caregivers - Mugure , Juliana Njeri (African Journal of Education,Science and Technology (AJEST), 2014)
Self-care is taking care of oneself as more often than not most caregivers are naturally inclined to take care of others. Caregivers let that work mentality “leak over” into the rest of their lives, allowing every relationship to become a caretaking relationship. Those drawn to work in caregiving may have learned at an early age to become other-focused rather than self-focused. As a result, they may not feel they need or deserve the same nurturing [that] they accept others need and deserve. They may have exceptionally high standards for themselves and yet be compassionate and forgiving of the shortcomings, mistakes or inconsideration of others. Watson‟s defines caring as a special way of being-in-relation with one‟s self, with others, and the broader environment. Such relationship requires both an intention and a commitment to care for the individual. Caregivers are people who take care of other adults, often parents or spouses, or children with special medical needs. The aim of writing this paper is to create awareness to the caregivers on the effects of care giving, bring to light the major roadblocks to caregivers, misconceptions held by the caregivers and encourage self-care to the caregivers. This will help the caregivers embrace the fact that the smallest changes can make the biggest impact. For example, never underestimate the power of a restful eight hours of sleep, exercise, good nutrition throughout the day, lunch with a friend can lift our spirits, taking a Sunday off to rest can help us recharge for the week.